The Master of Horror: A Glimpse into the Work and Legacy of H.P. Lovecraft - Manolopoulos, Dimitris; Karagiannakos, Maximos (Open Schools Journal for Open Science, 2025)
This presentation explores the life, work, and cultural impact of H.P. Lovecraft, one of the most significant yet misunderstood authors of the 20th century. It presents his personality, the social context in which he lived, and the literary themes he developed, focusing on his unique style of horror.